Sintesis Senyawa Heksapeptida Siklik Analog Pipecolisporin (Pro – Leu – Pip – Trp – Ala – Lys) Dengan Kombinasi Metode Sintesis Fase Padat Dan Fase Larutan Menggunakan Reagen Kopling Dic/Oxyma - Zahirotul Hikmah Fauziah; Nety Kurniaty; Rani Maharani (UNISBA Press, 2023)
Malaria, classified as a life-threatening disease, continues to exhinit a concerning surge in global cases annually. Admit the quest for novel antimalarial agents, the focus has turned towards peptide-based compounds, particularly the cyclic hexapeptide analogous to pipecolisporin, featuring the amino acid sequence (Pro – Leu – Pip - Trp – β-Ala – Ile) obtained from the isolation of endophytic fungus (Nigrospora oryzae) natural material. This study is dedicated to the synthesis of the pipecolisporin analog cyclic hexapeptide, bearing the amino acid sequence (Pro – Leu – Pip – Trp - Ala – Lys), employing a combined methodology. Specially, the solid-phase synthesis method (SPPS) is employed in the formation of linear hexapeptides, while the solution-phase synthesis method (LPPS) facilitates the generations of cyclic hexapeptides. These processes are facilitated by the DIC/Oxyma coupling reagents and implemented through the Fmoc strategy on 2-CTC resin. Preliminary results from the synthesis endeavors demonstrate the successful formation and characterization of linear hexapeptide compounds, yielding [M+H] values of 925.5394, alongside cyclic hexapeptide compounds, with [M-H] values of 708.11, as determined by mass spectrometry. Malaria termasuk kedalam salah satu golongan penyakit yang mengancam jiwa, dimana setiap tahunnya terjadi peningkatan kasus di seluruh dunia. Salah satu senyawa yang bermanfaat sebagai antimalaria baru berasal dari golongan peptida yakni heksapeptida siklik analog pipecolisporin dengan urutan asam amino (Pro – Leu – Pip – Trp – β-Ala – Ile) yang diperoleh dari hasil isolasi bahan alam jamur endofit (Nigrospora oryzae). Pada penelitian ini bertujuan untuk melakukan sintesis heksapeptida siklik analog pipecolisporin dengan urutan asam amino (Pro – Leu – Pip – Trp - Ala – Lys) menggunakan metode kombinasi yaitu metode sintesis fase padat (SPPS) pada proses pembentukan heksapeptida linear dan metode sintesis fase larutan (LPPS) pada proses pembentukan heksapeptida siklik dengan bantuan reagen kopling DIC/Oxyma serta strategi Fmoc pada resin 2-CTC. Berdasarkan tahapan sintesis yang telah dilakukan, hasil karakterisasi menggunakan spektrometer massa senyawa heksapeptida linear berhasil dibentuk dengan nilai [M+H] sebesar 925,5394 dan senyawa heksapeptida siklik dengan nilai [M-H] sebesar 708,11.